Jaw movement-related primary somatosensory cortical area in the rat. (22nd January 2015) - Uchino, K.; Higashiyama, K.; Kato, T.; Haque, T.; Sato, F.; Tomita, A.; Tsutsumi, K.; Moritani, M.; Yamamura, K.; Yoshida, A.
Highlights: Rostral part of the rat primary somatosensory cortex (S1) was electrically stimulated to evoke jaw-movements. Low-frequency long-train (LFLT) stimuli of the rostral S1 evoked jaw-movements and activated jaw-opening (JO) muscles. Most effective sites for LFLT stimuli overlapped those for high-frequency short-train stimuli in the rostralmost S1. The rostral S1 has projections to the lower brainstem areas including JO and jaw-closing premotoneurons. Jaw-movements evoked by rostral S1 stimulation are likely controlled by activation of its projections to the premotoneurons. Abstract: It has anatomically been revealed that the rostral part of the rat primary somatosensory cortex (S1) directly projects to the dorsal part of the trigeminal oral subnucleus (dorVo) and the dorsal part of juxtatrigeminal region (dorVjuxt), and that the dorVo and dorVjuxt contain premotoneurons projecting directly to the jaw-opening or jaw-closing motoneurons in the trigeminal motor nucleus (Vmo). However, little is known about how the rostral S1 regulates jaw movements in relation to its corticofugal projections. To address this issue, we performed intracortical microstimulation of the rat rostral S1 by monitoring jaw movements and electromyographic (EMG) activities. We for the first time found that low-frequency long-train stimulation of the rostral S1 induced single sustained opening of the jaw with elevated EMG activities of the anterior digastric muscles (jaw-opener). The effective sites for the low-frequency long-train stimulation overlapped the S1 sites where traditional high-frequency short-train stimulation was effective to induce single twitch-like jaw movement. We also found that the effective sites for the two kinds of train stimuli were included in the rostral S1 area, which has previously been identified to send direct projections to the dorVo or the dorVjuxt. Specifically, the most effective stimulation sites for the two kinds of train stimuli were located in the rostralmost part of S1 which has been reported to emanate strong direct projections to the dorVjuxt but less to the dorVo. Therefore, the present study suggests that the rat rostral S1, especially its rostralmost part, plays an important role in controlling jaw movements by activation of direct descending projections from the rostral S1 to the trigeminal premotoneuron pools, especially to the dorVjuxt.